(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: The vertebrate limb bud develops as an outgrowth of mesoderm, which forms all their elements (muscles, nerves, vessels, bone, cartilage, and tendon). Myogenic precursor cells are seen at E11.5 mouse embryo, when the first nerve fascicles begin to enter the limb. The first signs of musculature masses are seen at E12.5 in both fore and hind limb buds. Apoptosis or programmed cell death is essential in the development of the limbs. In vertebrate, the developing limb morphogenesis depends on the appropriate spatial and temporal balance between cell death and cell proliferation. Objective: To perform comprehensive analysis of the proximo-distal pattern of cell death, evaluated by (TUNEL test) in cross sections of mouse limbs during prenatal development after onset of primary myogenesis. Methods: Fifteen pregnant female mice (Musmusculus) were divided into three groups according to the days of pregnancy into day (14, 16 and 19), only two embryos were taken from each mouse. All the limb buds were involved in this study. Paraffin embedded histological cross-sections of the limb buds were prepared, histological staining (using H&E stain) and TUNEL test labeling were done. Assessment of the number of apoptotic cells in the limb bud mesenchyme was done by counting these cells. Results: The H&E stained sections of the limb buds showed less amounts of mesenchymal tissues in older embryos (day 19). The TUNEL stain showed active apoptotic changes at proximal parts of the limb buds at gestational day 19, while the distal parts of the limbs buds showed active apoptotic changes at the early days (day 14). The evaluation of TUNEL test reaction in the proximal regions showed statistical significant increase of apoptotic cells in day 19 compared to day 14 (p = 0.001 for both). The mean number of apoptotic cells in the proximal regions were statistically significant (p = 0.001) between day 16 and day 19. While the mean number of apoptotic cells of distal regions of the limb buds was higher at day 14 compared to that of day 16 and day 19. These differences between day 14 and day 16 were statistically significant and between day 16 and day 19 while statistically non-significant between day 14 and day 19. Comparison of mean number of apoptotic cells between proximal and distal regions in all the three groups showed a statistically significant higher mean number of apoptotic cells in the distal regions compared to proximal region (p = 0.001). The mean number of the apoptotic cells in both regions (proximal and distal) of the limb buds revealed statistically significant differences between day 16 and day 19 (p = 0.001). Conclusion: Apoptosis was higher in all parts of the developing limbs during day 19, and that could be associated with degenerative changes occurring at the apical ectodermal ridge. Moreover, apoptosis was higher in the distal part of the limb bud and this may be due to more differentiation of the distal parts than in the proximal part of the limb bud. Keywords: Development, limb bud, mouse, embryo, TUNEL, apoptosis, mesenchyme Citation: Al-Musawi DML, Mubarak HJ. Mesenchymal Cell death in mouse limb bud after the onset of primary myogenesis. Iraqi JMS. 2018; Vol. 16(1): 41-50. doi: 10.22578/IJMS.16.1.7